In situ CTD temperature, salinity, and oxygen observations in southern Mysingen, Stockholm archipelago, Sweden - Walther, Christoffer; Fredriksson, Jonas; Markgren, Joel; Frisk, Thomas (Swedish Defence University, 2026)
The dataset contains in situ CTD temperature and salinity observations from the southern Mysingen area in the Stockholm Archipelago. In situ dataset also contains oxygen measurements. The in situ data comprise vertical profiles collected during daytime at multiple stations, with high vertical resolution.
Data processing includes quality control of the in situ observations. Classified bottom-contact depth information was removed in accordance with applicable regulations, Swedish OSL 15§2. The dataset further contains oxygen measurements that have not been quality controlled and are not included in the associated analysis.
The dataset is organised into a single .csv file, with consistent time, depth, and geographical position references. File is in standard formats .CSV and can be accessed using commonly available software.

The dataset contains in situ CTD temperature and salinity observations from the southern Mysingen area in the Stockholm Archipelago. In situ dataset also contains oxygen measurements. The in situ data comprise vertical profiles collected during daytime at multiple stations, with high vertical resolution.
Data processing includes quality control of the in situ observations. Classified bottom-contact depth information was removed in accordance with applicable regulations, Swedish OSL 15§2. The dataset further contains oxygen measurements that have not been quality controlled and are not included in the associated analysis.
The dataset is organised into a single .csv file, with consistent time, depth, and geographical position references. File is in standard formats .CSV and can be accessed using commonly available software.
In situ CTD temperature, salinity, and oxygen observations in southern Mysingen, Stockholm archipelago, Sweden
Keywords: estuarine oceanography; oceanography; oceanografi; oceanography; oceanografi; Hydrography; Hydrografi; Sea regions; Havsområden; oceanography; oceanografi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav